Book review: Michele Lancione & Colin McFarlane, Global Urbanism: Knowledge, Power and the City. (November 2022) - Arun-Pina, Chan
Michele Lancione & Colin McFarlane, Global Urbanism: Knowledge, Power and the City . Routledge, 2021, 370pp, £27.99. ISBN 9780367745349.